2019
DOI: 10.1002/oby.22578
|View full text |Cite
|
Sign up to set email alerts
|

BMI and Labor Market Participation: A Cohort Study of Transitions Between Work, Unemployment, and Sickness Absence

Abstract: Objective This study aimed to test the hypotheses that individuals with obesity are at higher risk of unemployment and sickness absence and have a lower chance of getting employed compared with individuals with normal weight. Methods Data on weight and height were collected at baseline from 87,796 participants in the Danish National Health Survey 2010. Participants were then followed in national registers for 5 years. Outcome measures were transitions from employment to unemployment and sickness absence and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
3
21
1
Order By: Relevance
“…The present findings of an increased risk of LTSA associated with obesity in men are in line with those reported in previous studies . The effect size observed in our study (i.e., HR = 1.47‐1.81) was more or less equivalent to those reported in previous studies on LTSA (i.e., sick leave lasting for approximately 30 days or longer).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present findings of an increased risk of LTSA associated with obesity in men are in line with those reported in previous studies . The effect size observed in our study (i.e., HR = 1.47‐1.81) was more or less equivalent to those reported in previous studies on LTSA (i.e., sick leave lasting for approximately 30 days or longer).…”
Section: Discussionsupporting
confidence: 92%
“…More studies are needed to confirm whether the association between underweight and LTSA observed in our study also exists in Western countries despite the difference in social norms (e.g., working hours, work‐life balance, gender imbalance at workplace) . It should also be mentioned that previous studies on the association between underweight and SA of any duration reported conflicting results (positive association, inverse association, and no association) , which warrants further investigation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The impact of government policies to encourage individuals to postpone their retirement may be reduced if obesity limits work ability (defined as a worker's capacity to sustain employment in his or her current job, given the demands of the job and his or her individual resources) [9], thereby increasing the likelihood of premature exit from the labour market. Previous research has indicated that obesity may impact on an individual's work ability [10][11][12][13][14][15][16][17][18] which could, in turn, increase indirect societal costs (those resulting from reduced work productivity) [19][20][21]. According to at least one estimate, these may be greater than the direct health-care costs of obesity [22].…”
Section: Introductionmentioning
confidence: 99%